Junot Díaz : on the half-life of love - Saldívar, José David (Duke University Press, 2022)
"José David Saldivar's Junot Díaz is a literary study that takes a prismatic approach to the works and life of the Afro-Latino artist. Saldivar carefully traces the various themes and life events that influenced Díaz's writing-from childhood trauma to immigrant life to unusual writing processes. While this project is invested in telling the story of Díaz as a writer, an intellectual, and an activist, it is also a long reading of his Pulitzer Prize-winning novel The Brief Wonderous Life of Oscar Wao (2007). Because of its monumental impact on the course of US Latinx literature and new way of envisioning the decolonial world, Saldivar takes this novel as the heart of Díaz's oeuvre. Saldivar highlights the novel's germination, its connections with other critiques of colonialism, and its importance to understanding Díaz's fiction more generally."--